Between enthusiasm and indifference. Expectations and actions of the low and medium bureaucracy about the Civil Service Reform in two Peruvian ministries - Alva Mendoza, Jair (2018)
Peruvian civil service has been characterized as an element of low capability of the Peruvian state for being immersed in normative disorder (plenty of labor regimes) and for its non-existent planification. Thus, since 2008, a process of reforming the Peruvian civil service was started, said process has had as one of its main objectives to guarantee meritocratic access to public job positions of the Peruvian state. Nevertheless, with only two years left to achieve its main goal (2020), the transit of the different labor regimes to the regime of La ley Servir has not been has not been implemented yet. Having that on account, this study seeks to understand the expectations and actions of the low and medium bureaucracy on the effect that the civil service reform will have in the labor dynamics that have been developing in these workspaces To achieve said objective, two ministries are chosen: Education and Interior, for being two entities that started the procedures of the transit to the new labor regime in 2014, but to January of 2018 both had achieved a different progress. Thus, the labor dynamics of the low and medium bureaucracy are described; the causes of the current difference in the progress of the reform in both ministries are explained; and, finally the position and actions of the low and medium bureaucracy against the implementation of the civil service reform are analyzed. Starting with a examination of the documents and semi-structured interviews, we find out that the servers of the levels of bureaucracy studied show an agreement with the general objectives of Servir; nevertheless, they have two adverse positions to the reform: 1) both of them perceive that Servir has not informed correctly about the effects of the reform in their work; and 2) the implementation of the reform will not improve substantially the existing meritocracy in both ministries. This way, the study contributes to understand bureaucracy in front of internal institutional reforms of the Peruvian state.